Solving the unsolvable: Narrative practices in social work. Issue 3 (27th February 2017) - Paoletti, Isabella
Abstract : Social workers often confront situations that are practically, legally and morally unsolvable. Storytelling appears to be central to achieving what seems to be unobtainable and unsolvable. Drawing on past research on storytelling within the ethnomethodological tradition, this study aims to examine how storytelling is used in the discussion of very complex and delicate cases by social workers and other professionals. This study is based on data collected for the Aging, Poverty and Social Exclusion (APSE) project, based in Portugal. Through a detailed analysis within an ethnomethodological framework, and informed by conversation analysis of transcripts of inter-professional meetings, the study shows how social workers and other professionals (nurses, policemen, carer coordinators etc.) use stories in fine tuning the details of home visits, clients' housing conditions and so on. These stories are institutionally framed – that is, they are structured around what is considered right and wrong by a specific institutional gaze. Stories are often used to propose solutions, by telling the stories of similar previous cases. In these stories the professionals highlight their order of relevance and their responsibilities in managing the case. They delineate a sense of direction for social interventions conducted in narrow and tortuous paths, full of pitfalls.